Food insecurity and unmet healthcare needs in South Korea - Hwi Choe; Tae-Young Pak (BMC, 2023)
Abstract Background Food insecurity is a significant risk factor for chronic and infectious diseases. It is also a barrier to accessing healthcare because food insecurity tends to co-occur with other socioeconomic disadvantages. The objective of this study is to examine whether food insecure individuals in South Korea can access desired level of healthcare when needed. Methods This repeated cross-sectional study used data from the 2013-2015 and 2019-2021 waves of the Korean National Health and Nutrition Examination Survey. Multivariable logistic regression models were used to examine the association between household food insecurity and two indicators of unmet healthcare needs - any experience of forgoing medical service and the reasons for unmet needs (problems with availability, acceptability, and accessibility). Covariates indicating predisposing, enabling, and need factors were included in the regression analyses. Results Of the 19,394 participants aged 19-64 years, 4.5% were moderately food insecure, 0.9% were severely food insecure, and 9.3% reported unmet healthcare needs. In the adjusted model, moderate food insecurity (OR, 1.47; 95% CI, 1.19-1.82) and severe food insecurity (OR, 3.32; 95% CI, 2.27-4.85) were associated with higher odds of unmet healthcare needs in a dose-graded manner. These associations were largely due to the increased odds of accessibility-related unmet needs among participants with moderate (OR, 2.31; 95% CI, 1.68-3.19) and severe food insecurity (OR, 6.15; 95% CI, 3.91-9.68). Conclusions Food insecurity was associated with higher odds of unmet healthcare needs among Korean adults. Competing life demands may have a cumulative impact on health over the short and long term. Efforts to address trade-offs between healthcare needs and food insecurity may improve the health and well-being of marginalized populations.